2008
DOI: 10.1016/j.pain.2007.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Offset analgesia: A temporal contrast mechanism for nociceptive information

Abstract: Temporal filtering of afferent information is an intrinsic component of the processing of numerous types of sensory information. To date, no temporal filtering mechanism has been identified for nociceptive information. The phenomenon of offset analgesia, the disproportionately large decrease in perceived pain following slight decreases in noxious thermal intensity, however, suggests the existence of such a mechanism. To test the hypothesis that a temporal filtering mechanism is engaged during noxious stimulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 57 publications
5
113
1
Order By: Relevance
“…Typically, a drop in pain rating immediately after end of the transient is seen, representing pain inhibition. 95 Suprathreshold magnitude estimation of experimental pain is a simple-to-perform protocol, shown to be relevant in predicting acute postoperative pain. 1 The text will now update on the CPM phenomena, regarding methodology, mechanism, and clinical applications in diagnosis and in therapy for pain.…”
Section: Facilatory (Ts)mentioning
confidence: 99%
“…Typically, a drop in pain rating immediately after end of the transient is seen, representing pain inhibition. 95 Suprathreshold magnitude estimation of experimental pain is a simple-to-perform protocol, shown to be relevant in predicting acute postoperative pain. 1 The text will now update on the CPM phenomena, regarding methodology, mechanism, and clinical applications in diagnosis and in therapy for pain.…”
Section: Facilatory (Ts)mentioning
confidence: 99%
“…A slight increase in perceived pain occurred from the first to the second stimulus, and the third stimulus caused a significantly lower pain intensity compared with the first stimulus (although they had the same stimulus temperature). Studies have investigated the mechanisms involved in offset analgesia, and Yelle et al [72] concluded that offset analgesia is partly mediated by central mechanisms. In contrast, Derbyshire and Osborn [73] proposed that offset analgesia was caused by peripheral mechanisms.…”
Section: Offset Analgesiamentioning
confidence: 99%
“…These subjective pain dimensions wax and wane in the continued presence of a noxious stimulus (Greene and Hardy 1962). This temporal variability can occur due to peripheral and central phenomenon such as nociceptor adaptation (Torebjörk et al 1984) and central summation (Ochoa and Torebjörk 1989;Price and Dubner 1977;Torebjörk and Ochoa 1980), descending inhibition (Bouhassira et al 2003) or due to a change in stimulus properties (Davis and Pope 2002;Grill and Coghill 2002;Yelle et al 2008). However, the temporal pattern of specific pain qualities and their relationship with pain and affect is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Effect of static and dynamic heat pain stimulus profiles on the temporal dynamics and interdependence of pain qualities, intensity, and affect. J Neurophysiol 100: 1706 -1715, 2008. First published August 13, 2008 doi:10.1152/jn.90500.2008.…”
mentioning
confidence: 99%